Settlement of Dam During and End of Construction using Numerical Analysis - Kurniawati, Tri; Suryo, Eko Andi; Zaika, Yulvi (Rekayasa Sipil, 2024)
The construction process of the Tilong Dam induced significant settlement in the surrounding areas. This study aimed to enhance our understanding of the factors that influenced settlement behavior and improve the reliability of predictive models by using instrumentation data regarding the dam's vertical displacement. Numerical modeling was conducted to consider the actual embankment conditions and analyze the changes in the immediate settlement during and after construction. After the Tilong Dam construction, the measurements and numerical analysis showed settlements ranging from 0 to 832 mm. It was noted that settlements were expected during and after the construction, particularly at the dam's mid-sections. The back analysis method was employed to establish the values for material properties, specifically Young's modulus and Poisson's ratio, which affected the displacement. A multivariate regression comparison between the observed and predicted data yielded a determination coefficient (R²) of 0.914. This indicated a strong correlation between the observed and predicted values.